2014
DOI: 10.1111/nyas.12511
|View full text |Cite
|
Sign up to set email alerts
|

From policy coherence to 21st century convergence: a whole‐of‐society paradigm of human and economic development

Abstract: The 20th century saw accelerated human and economic development, with increased convergence in income, wealth, and living standards around the world. For a large part, owing to the well-entrenched Western-centric linear and siloed industrialization pattern, this positive transformation has also been associated with complex societal challenges at the nexus of agricultural, industrial, and health sectors. Efforts at cross-sectoral policy coherence have been deployed with limited success. To go beyond what has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 122 publications
0
36
0
Order By: Relevance
“…Considering the respective impact of different policies is not only technically challenging but is also inherently political (Ashoff, 2005;Verschaeve et al, 2016). For example, Dubé et al (2014) indicate that contradictions between policies that have been recognised as 'incoherencies' may well reflect political prioritisation of other policy goals over those associated with development. More broadly, policy coherence and development can be influenced and contested by multiple stakeholders, each with their own interests and differing relations of power (Knoll, 2014;Verschaeve et al, 2016).…”
Section: Conceptualising and Problematising Policy Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the respective impact of different policies is not only technically challenging but is also inherently political (Ashoff, 2005;Verschaeve et al, 2016). For example, Dubé et al (2014) indicate that contradictions between policies that have been recognised as 'incoherencies' may well reflect political prioritisation of other policy goals over those associated with development. More broadly, policy coherence and development can be influenced and contested by multiple stakeholders, each with their own interests and differing relations of power (Knoll, 2014;Verschaeve et al, 2016).…”
Section: Conceptualising and Problematising Policy Coherencementioning
confidence: 99%
“…Policy coherence has also increasingly been portrayed as a multi-level concept, 'vertically' applicable across global, international, national and sub-national policies and across the full range of countries that may be involved with or affected by development agendas (Dubé et al, 2014;OECD, 2016). Further, consideration of the 'horizontal' coherence of policy implementation has expanded to encompass private and civil society organisations as well as institutions in the public sector (Janus et al, 2015;OECD, 2016).…”
Section: Conceptualising and Problematising Policy Coherencementioning
confidence: 99%
“…This type of policy framework would be very beneficial to scale up the Odisha CI pilot and, in general, would be very supportive to realizing multidimensional outcomes. However, framing and implementing such policies would require cutting across departmental silos, very much along the lines of the whole‐of‐government model outlined by Dubé et al …”
Section: Discussionmentioning
confidence: 99%
“…Second, and most importantly, research on cross-sectoral policy coherence has demonstrated that policies supporting healthy diets require coordination and capacity to work pragmatically across organizational, sectoral, and jurisdictional boundaries [86]. The various actors may have a range of capacity and work on different time scales, for example, because of their specific political cycles.…”
Section: Methodsmentioning
confidence: 99%